PtRu nano-dandelions on thiolated carbon nanotubes: a new synthetic strategy for supported bimetallic core-shell clusters on the atomic scale - Kim, Yong-Tae; Lee, Hyunjoo; Kim, Hyoung-Juhn; Lim, Tae-Hoon (ROYAL SOC CHEMISTRY, 2010)
Core-shell PtRu clusters resembling dandelions were formed on thiolated carbon nanotubes by the difference in bond strength with surface thiol groups between Pt and Ru single atoms. The formation mechanism was clearly understood using a different release timing concept based on EXAFS and XPS analyses during heat treatment.
Keywords: NANOPARTICLES; PLATINUM; STABILITY; SINGLE